Characterizing Service-Learning Partnerships in Engineering Through the Experiences of Undergraduate Students - David A. Delaine; Julia Thompson (The University of Alabama, 2022)
Partnerships are a central part of the service-learning experience. Recent research has focused on partnerships, types of interactions, and relationships across service-learning from various perspectives, yet examinations of service-learning partnerships from the student perspective, specifically the relationship between the community partner and the student, are limited. This investigation answers two research questions: (a) How do undergraduate engineering students characterize the nature of service-learning partnerships? and (b) What factors within service-learning influence student perspectives on partnerships? Focus groups and interviews were conducted with students who engaged in service-related engineering experiences, and the transcriptions of these discussions were analyzed using the transactional, cooperative, and communal framework, a method of thematic discourse analysis. Results revealed that the experiences of undergraduate students in service-learning provide valuable insight for analyzing partnerships, specifically with respect to the following themes: service component, social context, and community interactions. The factors shown to influence students' perspectives of the service-learning partnership include the positionality of the students and the intentionality of the instructors. Our results imply that student experiences hold value beyond what is currently leveraged for research, teaching, and community outcomes. This study provides evidence that service-learning and community engagement efforts benefit when they are designed and evaluated in ways that acknowledge student voices and embrace students as knowledgeable and valuable members of university-community partnerships.